2019
DOI: 10.3389/fpsyg.2019.02284
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Regulation Behaviors on University Students’ Intentions of Persistance

Abstract: The implementation of the European higher education area (EHEA) is a true paradigm change in university education in which the student, with particular consideration given to autonomous work, takes the place of the teacher as the central element of the teaching-learning process. In this autonomous work, the strategies the students regularly use become particularly important, given the supposition that doing that work will lead to academic success. The objective of this study is to analyze the variables that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…There is academic evidence that PLSR and CIU are positively associated. The relationship between PLSR and CIU was studied in Concannon et al (2018) and Bernardo et al (2019). Bernardo et al (2019) found that integrating self-regulation strategies in the educational process increases the intention to persist in the course.…”
Section: Learning Level Intenɵonmentioning
confidence: 99%
See 1 more Smart Citation
“…There is academic evidence that PLSR and CIU are positively associated. The relationship between PLSR and CIU was studied in Concannon et al (2018) and Bernardo et al (2019). Bernardo et al (2019) found that integrating self-regulation strategies in the educational process increases the intention to persist in the course.…”
Section: Learning Level Intenɵonmentioning
confidence: 99%
“…The relationship between PLSR and CIU was studied in Concannon et al (2018) and Bernardo et al (2019). Bernardo et al (2019) found that integrating self-regulation strategies in the educational process increases the intention to persist in the course. Similarly, Concannon et al (2018), in their phenomenological study, found that courses that are designed to improve learners' perceived self-regulation strengthen their persistence on the course and their intention to take similar courses in the future.…”
Section: Learning Level Intenɵonmentioning
confidence: 99%
“…Particularly, Tinto (1975) claimed that "dropout represents the failure of individuals, of given ability and goal commitment, to achieve desired educational goals" (p. 78). In line with this definition, student dropout is from an individual perspective associated with dysfunctional self-regulation (Achtziger & Gollwitzer, 2010;Bernardo et al, 2019;de la Fuente-Arias, 2017;Nota et al, 2004). Heublein and Wolter (2011) extended this view to a perspective that also considers environmental factors: The authors conceptualized student dropout as a complex event where individual, institutional, and social factors that affect studying are superimposed.…”
Section: Conceptualizing Student Dropoutmentioning
confidence: 99%
“…Here, focusing on individual determinants is particularly interesting, since these have a direct influence on the course of studies (Gensch & Kliegl, 2012). Especially individual determinants such as test anxiety or a lack of motivation in self-regulated learning have increasingly been analyzed in association with student dropout (Bardach et al, 2019;Bernardo et al, 2019;Blüthmann et al, 2008;Respondek et al, 2017;Schnettler et al, 2020a, b). Hence, it is of great interest to take a closer look at these correlates of student dropout when analyzing its process-as it can be assumed that different phases of developing a dropout intention relate to a different degree to them.…”
Section: Correlates Associated With Student Dropoutmentioning
confidence: 99%
“…Here, academic skills provide a crucial stepping-stone to the solution. Academic skills have been consistently shown to promote students' performance, attrition intentions, and actual attrition behavior (Bean and Metzner, 1985;Rovai, 2003;Robbins et al, 2004;Credé and Kuncel, 2008;Cathey et al, 2016;Hattie and Donoghue, 2016;Bernardo et al, 2019).…”
Section: Academic Skillsmentioning
confidence: 99%